Implementation of Basic Local Alignment Search for Detection H1N1 Sequence Alignment - Retno Tri Vulandari; Sri Siswanti; Andriani Kusumaningrum Kusumawijaya; Kumaratih Sandradewi (International Journal of Trends in Mathematics Education Research, 2019)
Bioinformatics is a science that studies the management and analysis of biological information. Bioinformatics includes application of mathematics, statistics, and informatics to biological problems to solve. Bioinformatics can store data generated by the genome project with regular and high degree of accuracy. Basic local alignment search is one of the methods used to process penyejajaran molecular data sequences. In 2009, there is a virus that attacks the respiratory tract that is the swine flu. The virus is spread around the world, so that retrieved the journal research on diverse virus DNA sequences in different endemic countries. Therefore, in this study will be explained about the process sequence alignment of the H1N1 swine flu virus. H1N1 Weiss AF 250365.2 and H1N1 Swine AF250364.2 have 90% similarity level.